ORGANIZATIONAL COMMUNICATION STRATEGY IN SHAPING THE LEADERSHIP CHARACTERS OF THE LEADERS IN OIL AND GAS ACADEMY (AKAMIGAS), INDRAMAYU - Zaelani Adnan, Ahmad; Ahman, Eeng; Fattah, Nanang; Yuniarsih, Tjutju; Disman, Disman; Hadi Senen, Syamsul; Suwatno, Suwatno (Dinasti Publisher, 2020)
Communication acts as an instrument for everyone to interact both in formal and informal matters in daily life. The purpose of this study was to analyse organizational communication strategies in shaping the leadership character of the leaders of the Indramayu Oil and Gas Academy (AKAMIGAS). This study uses a qualitative approach, by determining the informants using purposive sampling and snowball sampling. Data collection techniques are using observation and interviews. Based on the results of research and discussion that structured information dissemination using the institution's primary online media as a communication strategy, team work, and leadership competency training are strategies used to form leadership characters that must be nurtured by the organization. Based on the results that the author has carefully examined, by conducting observations and interviews in the organization of communication strategies conducted using downward communication and upward communication. With these two ways communication strategies can be carried out with leaders and subordinates as the creation of communication that influences the organization's progress